Seismic Vulnerability Analysis and Retrofitting of the SS. Rosario Church Bell Tower in Finale Emilia (Modena, Italy) - Formisano, Antonio; Milani, Gabriele (Frontiers in Built Environment, 2019)
The Italian territory is rich of constructions belonging to the architectural heritage which deserve to be protected against earthquakes. In seismic prone areas ecclesiastic complexes, including churches, bell towers, monasteries, basilicas, synagogues, cathedrals and so on, have shown to be very susceptible at damage, even with partial or total collapses, when undergoing earthquakes. Indeed, these constructions, which are usually designed to withstand gravity loads only, are characterised by slender walls, lack of horizontal floors, bad quality of the masonry apparatus, ineffective connections among walls and between roof and walls and absence of tie-beams able to absorb the thrusts of arches and vaults. All these issues are responsible of the damages suffered by these structures, as detected after the last Italia earthquakes, such as those occurred in L’Aquila (2009), Emilia-Romagna (2012), Central Italy (2016) and Ischia (2017). In the current paper the seismic vulnerability assessment of the bell tower of the SS. Rosario ecclesiastic complex in Finale Emilia (district of Modena, Italy) is presented and discussed. After the geometrical and structural surveys of the whole masonry structure have been performed, the global seismic analysis of the bell tower by the 3Muri analysis software has been done. In particular, the behavioural differences between the isolated condition of the tower and the case within the ecclesiastic complex have been highlighted, showing the aggregate beneficial effect. Finally, proper retrofitting interventions have been designed and applied to the masonry bell tower, considered both as isolated construction and aggregate one, and the different benefits deriving from these interventions in the two inspected cases have been emphasised.